Legal Analysis of Business Licensing by Umrah Pilgrimage Organizers as A Form of Legal Protection for Prospective Umrah Pilgrimages - Anggun Estu Aryaningsih; Nunik Nurhayati (Universitas Muhammadiyah Surakarta, 2025)
Umrah is a series of worship activities that include tawaf, sa'i, and tahallul which are regulated by the guidelines of the Qur'an and Sunnah. This study analyzes legal protection for prospective Umrah pilgrims and licensing regulations for Umrah Pilgrimage Travel Organizers (PPIU) based on the Regulation of the Minister of Religion Number 5 of 2021 concerning Standards for Umrah Pilgrimage Travel Organization Business Activities and Special Hajj Pilgrimage Organizations (PMA No. 5 of 2021). PPIU must comply with regulatory standards including obtaining business permits, maintaining transparent financial practices, and providing legal protection for pilgrims to avoid fraud or illegal bureaus. The increasing cases of Umrah travel fraud require strengthening regulations so that pilgrims receive legal protection. This study uses a normative legal approach with a qualitative analysis method. The results of this study indicate that legal protection for Umrah pilgrims consists of preventive and repressive aspects. This regulation regulates the legal requirements for PPIU, monitoring mechanisms, and administrative sanctions. Preventive protection is realized through information transparency and supervision of PPIU, while repressive protection is provided through complaint mechanisms and dispute resolution. This study offers a specific analysis of the legal protection of prospective pilgrims based on the latest regulations, differentiating it from previous, more general studies. This regulation is expected to minimize the risk of fraud and increase the professionalism of Umrah travel organizers.